Dopamine-related genes and spontaneous smoking cessation in ever-heavy smokers. (August 2011) - Breitling, Lutz P; Müller, Heiko; Illig, Thomas; Rujescu, Dan; Winterer, Georg; Dahmen, Norbert; Nitz, Barbara; Raum, Elke; Rothenbacher, Dietrich; Brenner, Hermann
Several studies have provided evidence for associations of polymorphisms located in and near dopamine-related genes and nicotine dependence and other smoking-related phenotypes, including pharmacogenetic interactions.Aim: The purpose of the present work was to examine the association of SNPs in the DOPA decarboxylase ( DDC ), dopamine receptor D2 ( DRD2 ) and dopamine transporter ( SLC6A3 ) genes with smoking cessation in a large retrospective study featuring approximately 900 cessation events.Materials & methods: Data originated from the enrollment questionnaire of the epidemiological ESTHER study of community-dwelling adults aged 50–74 years, conducted in the German state of Saarland between July 2000 and December 2002. Restricting the analyses to subjects who reported to have regularly smoked >20 cigarettes per day at some point in their life, we used survival analysis methods to model the time from initiation of regular smoking to cessation (defined as quitting with abstinence lasting until enrollment) and its relation with eight polymorphisms in the aforementioned genes (five in DDC, two in DRD2 and one in SLC6A3 ) in 1446 participants.Results: Neither individual variants nor DDC haplotypes were associated with the probability of overcoming nicotine dependence in this cohort.Conclusion: The repeated suggestion of associations between the variants examined and nicotine dependence in previous reports seems to contrast the negative results in the present study. This would appear consistent with the hypothesis that the establishment of regular heavy smoking might abolish associations between genetic determinants of nicotine dependence and nicotine dependence-related phenotypes, in particular the probability of successful smoking cessation. Original submitted 15 February 2011; Revision submitted 2 May 2011